Building a Progressive Reproductive Law in South Africa - Donrich Thaldar (Harvard FXB Center for Health and Human Rights, 2023)
This article delves into the expansion of procreative freedom in relation to assisted reproductive technologies (ARTs) in South African law, with reference to three seminal cases. In the case of AB v. Minister of Social Development, the minority of the South African Constitutional Court held that the constitutional right to procreative freedom is applicable to ARTs. Importantly, both the minority and the majority agreed on the principle of procreative non-maleficence-the principle that harm to the prospective child constitutes a legitimate reason to limit the procreative freedom of the prospective parents. Following this, Ex Parte KF2 clarified the concept of the "prospective child" as relating to an idea, rather than an embryo. Finally, in Surrogacy Advisory Group v. Minister of Health, the controversial issue of preimplantation sex selection for non-medical reasons was examined. The court confirmed that the use of ARTs falls within the ambit of procreative freedom. While holding that preimplantation sex selection for non-medical reasons is inherently sexist, the court found that a woman's right to procreative freedom-including the sex identification of an in vitro embryo-outweighs other considerations. These landmark cases establish a robust groundwork for a progressive reproductive law in South Africa.